PEMANFAATAN PENERIMAAN NEGARA BUKAN PAJAK DI BIDANG KEHUTANAN DALAM MELESTARIKAN FUNGSI LINGKUNGAN* - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2009)
Payment for environmental services through reforestation fund to maintain forest sustainability conforms with the effort to terminate deforestation. However, its effectivity is questionable as it is often used to finance other activities. This research aims to analyze non-tax state revenue from forestry field, specifically its relation to environmental protection efforts.